(untitled) (Pulse, 2018)
Background: Chikungunya viral infection in Bangladesh has marked 2017 summer with unprecedented magnitude for the first time. Chikungunya virus (CHIKV) and Dengue virus (DENV) are arboviruses that share the same Aedes mosquito vectors and thus overlap in their endemic areas.These two viruses cause similar clinical presentations, especially in the initial stages of infection. Because the outcomes and management strategies for these two viruses are different, early and accurate diagnosis is imperative. Early diagnosis is also important for surveillance and outbreak control. Objective: As virus isolation is not undergoing in the country and antigen based commercial detection assay is not available for CHIKV we used one step real time reverse transcriptase polymerase chain reaction (RT-PCR) method to detect and discriminate CHIKV and DENV in blood during suspicious clinical symptoms. Results: By this RT-PCR method we have detected 603 cases of CHIKV and 233 cases of DENV and thus facilitated rapid diagnosis and clinical management in the recent CHIKV outbreaks in the country. Conclusion: This is the first report about molecular detection and differentiation of CHIKV and DENV at time of clinical presentation and further show evidence of simultaneous outbreaks of both the viral infections in the country. Pulse Vol.10 January-December 2017 p.6-11